2019
DOI: 10.1161/strokeaha.118.023902
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose— Early prediction of clinical outcome after aneurysmal subarachnoid hemorrhage (aSAH) is still lacking accuracy. In this observational cohort study, we aimed to develop and validate an accurate bedside prediction model for clinical outcome after aSAH, to aid decision-making at an early stage. Methods— For the development of the prediction model, a prospectively kept single-center cohort of 1215 aSAH patients, admitted between 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 33 publications
6
84
0
Order By: Relevance
“…The majority of previously established aSAH outcome prediction models are based on neurological deficits on admission and radiographic features, such as thickness of subarachnoid blood clots and the presence of IVH or ICH. However, more recent evidence suggests that other factors play a role in precise outcome prediction, such as patient age, pupil status, and aneurysm size and location [21,29]. The inclusion of a high number of variables is one of the main strengths of ML approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previously established aSAH outcome prediction models are based on neurological deficits on admission and radiographic features, such as thickness of subarachnoid blood clots and the presence of IVH or ICH. However, more recent evidence suggests that other factors play a role in precise outcome prediction, such as patient age, pupil status, and aneurysm size and location [21,29]. The inclusion of a high number of variables is one of the main strengths of ML approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Other recently published aSAH prognostic models which were based on large-scale aSAH-cohorts include the SAFIRE scale, FRESH score and different scores based on the SAHIT cohort [26][27][28] . The SAFIRE model predicted poor functional outcome with an AUROC of 0.73 in the validation cohort and was based on aneurysm size, age, Fisher grade and WFNS 26 . The FRESH score considered variables H&H, age, APACHE-II Physiologic score and aneurysmal rebleed within 48 hours 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid hemorrhage Fisher grade was observed as an important factor in our study, being significantly different in the bad QOL group in comparison with the good QOL group with good functional outcome in group H. As we all well-know, the severity of subarachnoid hemorrhage Fisher grade is associated with the rate of occurrence of delayed cerebral vasospasm. Some previous studies demonstrated that Fisher grade was a risk predictor for delayed cerebral infarction (40,41). Therefore, we hypothesized that a higher Fisher grade might contribute to a higher possibility of delayed cerebral infarction, which would result in lower cerebral perfusion and would influence the rehabilitation of patients at follow-up.…”
Section: Discussionmentioning
confidence: 93%